Kampanye Konservasi Sungai Di Kuningan Melalui Animasi Pendek - Yulyanto; Rika Nugraha; Abi M Rasul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The increase in population has also resulted in changes in the pattern of people's consumption of water sources, but today there are still many people who are still not aware of maintaining their water sources including rivers, in Kuningan, especially in the Kuningan village area, there are rivers that used to be clean slowly become dirty due to garbage and waste, the purpose of this research is so that the community, especially children, know more about the importance of protecting the environment, especially the rivers around it. The results of this study made a short animated film entitled Tirta & Yahsa